2022
DOI: 10.14740/gr1508
|View full text |Cite
|
Sign up to set email alerts
|

Flood Syndrome

Abstract: Flood syndrome refers to the exsanguination of ascitic fluid following the spontaneous rupture of an umbilical hernia, and is a rare complication of liver cirrhosis with ascites. In this case report, we describe a 67-year-old patient with Flood syndrome who was initially managed conservatively in a community hospital run by primary care physicians, prior to transfer to a tertiary hospital for specialist surgical review and management. We also performed a literature review of the current treatment modalities to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Given the rarity of this condition, the approach to management is not standardized and the majority of published data stems from case reports and case series [ 3 , 4 ]. Prior reviews reported that medical-only management had mortality rates of 60–80% compared with 6–20% involving combined medical and surgical intervention [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the rarity of this condition, the approach to management is not standardized and the majority of published data stems from case reports and case series [ 3 , 4 ]. Prior reviews reported that medical-only management had mortality rates of 60–80% compared with 6–20% involving combined medical and surgical intervention [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative medical management may include salt restriction, diuretics, electrolyte monitoring, wound dressings, antibiotics, ostomy pouches and fibrin glue. Multiple surgical approaches have been attempted including pigtail drains, partial splenic embolization [ 5 ], temporary percutaneous peritoneal drainage, peritoneovenous shunt, transjugular intrahepatic portosystemic shunt and most commonly, repair of the umbilical hernia with or without a mesh [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flood in 1961. 2 Ascites, a common complication of liver cirrhosis, affects nearly half of the population with this condition. Large-volume ascites significantly impairs the patients' ability to perform daily activities.…”
mentioning
confidence: 99%